Bioinformatics analysis to identify action targets in NCI-N87 gastric cancer cells exposed to quercetin - Yun Zeng; Zhengjie Shen; Wenzhe Gu; Mianhua Wu (Taylor & Francis Group, 2018)
Context: Quercetin exerts antiproliferative effects on gastric cancer. However, its mechanisms of action on gastric cancer have not been comprehensively revealed. Objective: We investigated the mechanisms of action of quercetin against gastric cancer cells. Materials and methods: Human NCI-N87 gastric cancer cells were treated with 15 μM quercetin or dimethyl sulfoxide (as a control) for 48 h. DNA isolated from cells was sequenced on a HiSeq 2500, and the data were used to identify differentially expressed genes (DEGs) between groups. Then, enrichment analyses were performed for DEGs and a protein-protein interaction (PPI) network was constructed. Finally, the transcription factors (TFs)-DEGs regulatory network was visualized by Cytoscape software. Results: A total of 121 DEGs were identified in the quercetin group. In the PPI network, Fos proto-oncogene (FOS, degree = 12), aryl hydrocarbon receptor (AHR, degree = 12), Jun proto-oncogene (JUN, degree = 11), and cytochrome P450 family 1 subfamily A member 1 (CYP1A1, degree = 11) with higher degrees highly interconnected with other proteins. Of the 5 TF-DEGs, early growth response 1 (EGR1), FOS like 1 (FOSL1), FOS, and JUN were upregulated, while AHR was downregulated. Moreover, FOSL1, JUN, and Wnt family member 7B (WNT7B) were enriched in the Wnt signaling pathway. Discussion and conclusions: CYP1A1 highly interconnected with AHR in the PPI network. Therefore, FOS, AHR, JUN, CYP1A1, EGR1, FOSL1, and WNT7B might be targets of quercetin in gastric cancer.